Serogroup C invasive meningococcal disease in the post-vaccine era and vaccine failures - Neus Rius; Mayli Lung; Carolina Fernández-San José; Tamara Iglesias; Juliana Esperalba; Fernado A. Moraga-Llop; Pere Soler-Palacín (Elsevier, 2020)
Introduction: The incidence of serogroup C invasive meningococcal disease (IMD) has decreased since the introduction of systematic vaccination in 2000 The aim of this study is to determine the number serogroup C IMD cases diagnosed since then and the vaccine failures. Patients and methods: A retrospective analysis was performed on patients diagnosed with IMD by culture or polymerase chain reaction (PCR) in a maternity and childhood hospital in Barcelona between 2001 and 2018. An analysis was made of the number of vaccine doses and the age received, as well as on the medical records and vaccine cards. Results: There were 128 confirmed cases of IMD (7.1 cases/year; 70.3 in <5 years). The serogroup was studied in 125 (97.6%) cases, in which 103 (82.4%) were B, 10 (8%) were C, 1 (0.8%) was 29E, and 1(0.8%) was Y, and only 10 (8%) were not able to be serogrouped. Of the 10 patients with serogroup C, 4 were not vaccinated, and in 3, the course was not complete as regards the number of doses. The other 3 received the complete course according to age and current calendar, and thus were considered vaccine failures. A total of 6 patients died (mortality rate: 4.7%), 5 due to serogroup B (mortality: 4.8%), and 1 due to serogroup C (mortality: 10%). Conclusions: Serogroup C only represented 8% (10 cases) of IMD cases in the period studied, 3 cases due to this serogroup being vaccine failures. Resumen: Introducción: La incidencia de la enfermedad meningocócica invasiva (EMI) por serogrupo C ha disminuido desde la introducción de la vacunación sistemática en 2000. El objetivo de este estudio es determinar los casos de EMI diagnosticados desde entonces y los fallos vacunales en los casos por serogrupo C. Pacientes y métodos: Análisis retrospectivo de pacientes diagnosticados de EMI confirmada por cultivo o reacción en cadena de la polimerasa, en un hospital materno infantil de tercer nivel de Barcelona, entre 2001 y 2018. Se analizó el número de dosis de vacuna recibidas y la edad, recogidos de la historia clínica y del carnet de vacunaciones. Resultados: Se confirmaron 128 casos de EMI (7,1 casos/año; 70,3% en <5 años). Se estudió el serogrupo en 125 casos (97,6%): 103 fueron B (82,4%), 10 fueron C (8%), 1 fue 29E (0,8%) y 1 fue Y (0,8%); solo 10 (8%) no fueron serogrupables. De los 10 pacientes con serogrupo C, 4 no estaban vacunados y en 3 la pauta fue incompleta en cuanto a número de dosis; 3 de ellos recibieron la pauta completa según la edad y el calendario vacunal vigente, por lo que se consideran fallos vacunales. Fallecieron 6 pacientes (tasa letalidad: 4,7%): 5 por serogrupo B (letalidad: 4,8%) y 1 por serogrupo C (letalidad: 10%). Conclusiones: El serogrupo C representó solo el 8% (10 pacientes) de los casos de EMI en el periodo de estudio siendo 3 de los casos por este serogrupo fallos vacunales.